Changes of dream and BDNF proteins expressions, pro-inflammatory and oxidative stress levels spinal cord of streptozotocin-induced painful diabetic neuropathy rats upon minocycline and ifenprodil treatments - Ismail, Che Aishah Nazariah (2018)
Diabetic neuropathy (DN) is a long-term complication of diabetes mellitus (DM) which could be painful (PDN) or non-painful (non-PDN). This study aimed to explore the effect of minocycline and ifenprodil on the (i) proteins expressions of NR2B subunit (NR2B) and phosphorylated NR2B subunit (phospho-NR2B) of Nmethyl- D-aspartate (NMDA) receptors, microglial activation, brain-derived neurotrophin factor (BDNF) and Downstream Regulatory Element Antagonist Modulator (DREAM) proteins), (ii) pro-inflammatory cytokines (interleukin-1β (IL- 1β) and tumour necrosis factor-α (TNF-α) and (iii) oxidative stress markers (malondialdehyde (MDA), superoxide dismutase (SOD) and catalase) in the pathogenesis of DN in the spinal cord of streptozotocin-induced diabetic rats. One hundred and sixty-eight Sprague-Dawley male rats were assigned into seven groups (n=24) consisting of non-diabetic control (S+CB), diabetic PDN control (S+STZ), diabetic non-PDN control (non-PDN), minocycline-treated PDN groups (M 80 and M 160) and ifenprodil-treated PDN groups (I 0.5 and I 1.0). DM was induced with a single streptozotocin injection at 60 mg/kg. Nociceptive behavioural tests such as Von Frey, hot-plate and formalin tests were conducted to assess tactile allodynia, thermal hyperalgesia and chemical hyperalgesia respectively. Treatment of either saline, minocycline (80 μg/day or 160 μg/day) or ifenprodil (0.5 μg/day or 1.0 μg/day) was administered intrathecally for seven days. Chronic inflammatory pain was inducedwith formalin injection before being sacrificed three days later. The spinal cord lumbar enlargement region was collected for immunohistochemistry, Western Blot (WB) and enzyme-linked immunoabsorbent assay (ELISA) analyses. The results showed that PDN rats developed tactile allodynia and chemical hyperalgesia but not thermal hyperalgesia, in which were prevented by minocycline and ifenprodil at both lower and higher doses used. Meanwhile, non-PDN group showed lower tactile allodynia, thermal and chemical hyperalgesia. There was significant higher NR2B, activated microglia, BDNF and DREAM proteins ipsilaterally and contralaterally by immunohistochemistry and WB analyses in (S+STZ) group, in which the results were reduced in non-PDN group. Minocycline and ifenprodil at both lower and higher doses significantly attenuated the expressions and mean relative NR2B, phospho-NR2B, BDNF, DREAM proteins levels and activated microglial positive neurons in a dosedependent manner. Furthermore, (S+STZ) and non-PDN groups showed a significant higher TNF-α level. Minocycline inhibited both cytokines. Moreover, MDA level was significantly higher in (S+STZ) and non-PDN groups. Significant lower catalase enzyme activity with insignificant SOD enzyme activity was detected in (S+STZ) group whilst marked higher catalase activity with lower SOD enzyme activity were detected in non-PDN group. Minocycline and ifenprodil attenuated MDA level and lead to higher catalase and SOD activities in the spinal cord. In conclusion, minocycline and ifenprodil is effective to combat PDN through their strong antinociceptive, anti-oxidant and anti-inflammatory activities as has been shown in this study.